PENGEMBANGAN MEDIA ROLE PLAYING CARDS UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SSIWA KELAS IV SEKOLAH DASAR - Eka Dwi Nengsih; Liyana Sunanto (PT. Hasba Edukasi Mandiri, 2025)
Speaking ability is one of the essential language skills in Indonesian language learning at the elementary level. However, in practice, students often face difficulties expressing ideas orally due to conventional learning approaches and limited communicative activities. This study aims to develop Role Playing Cards media as an interactive learning tool to improve the speaking skills of fourth-grade students at UPTD SDN 2 Karangkendal. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The subjects were 30 fourth-grade students. The media was designed using Canva and enhanced with CapCut for video-based support. Validation results from media and material experts indicated a feasibility percentage of 91.8%, categorized as very feasible. Classroom implementation revealed a significant improvement in students’ speaking performance, with the average pre-test score increasing from 67.3 to 85.6 in the post-test, and an N-Gain Score of 0.67, categorized as moderate to high improvement. These findings suggest that the Role Playing Cards media is effective for enhancing elementary students’ speaking skills in Indonesian language learning.